Use of e-cigarettes among young queer men living in Aotearoa New Zealand - Judith McCool; Peter Saxton; Rosie Dobson; Thibaut Bouttier-Esprit (CSIRO Publishing, 2023)
Introduction Queer-identifying (non-heterosexual) men report higher rates of tobacco and e-cigarette use than the general population. The advent of e-cigarettes as a commercial product in Aotearoa New Zealand has been accompanied by aggressive marketing and a sharp uptake in use, especially among young people. Recent evidence suggests that e-cigarettes are widely used for purposes other than smoking cessation. Aim This study investigated how vaping is perceived and the role e-cigarettes play in the daily lives of young queer users. Methods Using focus groups with a semi-structured interview proforma, we interviewed twelve young queer men between July and August 2021. Interviews were queer-led, conducted via Zoom, and lasted up to 2 h. Interviews were audio-recorded and transcribed verbatim for subsequent inductive and thematic analysis. Results Of the twelve participants, 10 were daily users, and two described themselves as 'social vapers'. We found strong evidence for minority and intra-minority stress as a driver to uptake and continued use of e-cigarettes. E-cigarettes were also used to navigate new social and cultural spaces and as currency for integration into various social milieux, including both mainstream and gay community spaces. There was little support for queer-targeted cessation initiatives. Discussion Vaping is highly socially acceptable within queer communities where it is a facilitator of social integration, managing stress and quitting tobacco.